Analisis Aktivitas Otot Dengan Perbedaan Jenis Kelamin Pada Postur Tangan Menggunakan Surface Electromyography - Indah Pratiwi; Purnomo Purnomo; Rini Dharmastiti; Lientje Setyawati (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2017)
This study aims to analyze the muscle activity in the upper body of the hand posture. Measurements are made when the workers perform the activities of making pottery in a sitting position. Measurements use surface electromyography and differentiate sex between men and women. The research steps were: (1) worker capture resulted in ten postures, (2) determination of muscle influences, namely: extensor carpi radialis muscle, extensor carpi ulnar muscle, extensor of the wrist muscle, biceps brachii muscle, flexor carpi radialis muscle, and (5) calculate using root mean square (RMS) and RMS value index RMS value and deviation index RMS value of male - higher than women in each muscle and in every posture.